Courtroom contrition: how do judges know?*. Issue 3 (3rd July 2018) - Rossmanith, Kate; Tudor, Steven; Proeve, Michael
ABSTRACT: In most common-law jurisdictions world-wide, an offender's remorse is a well-settled mitigating factor in sentencing, with judges obliged to take it into account when formulating an offender's sentence. However, the importance of remorse in sentencing is matched by its mystery. Given remorse's central role in the moral drama of the criminal justice process, it is crucial to investigate how remorse is evaluated, and also to understand the limitations of those evaluations. The present article seeks to contribute to that effort by exploring what is involved in judges coming to know — and claiming to know — that 'this offender is remorseful'. Drawing on in-depth original interviews with 20 magistrates and judges in New South Wales, Australia, we explore how judges themselves understand their own ways of knowing about remorse. We then look at two basic scenes of offender remorse: remorse in the courtroom and remorse outside the courtroom. Many judges want to see remorse in the courtroom, and are often confident that they know it when they see it. But, at the same time, as we shall see, many judges also want evidence of the offender's remorse outside the courtroom.